Type‐I interferons in Parkinson's disease: innate inflammatory response drives fate of neurons in model of degenerative brain disorder: An editorial comment on 'Type‐I interferons mediate the neuroinflammatory response and neurotoxicity induced by rotenone'. Issue 1 (April 2017) - Kanninen, Katja M.; White, Anthony R.
Abstract : Read the commented article 'Type‐I interferons mediate the neuroinflammatory response and neurotoxicity induced by rotenone' on page 75 . Abstract : Rotenone induces up‐regulation of type‐I interferons (IFN‐I) from microglia and astrocytes. These cytokines interact with neurons and also drive release of further pro‐inflammatory cytokines from glial cells and neurons. The combined pro‐inflammatory assault results in neuronal cell death. This is a new understanding of how rotenone drives neurotoxicity through IFN‐I inflammation. Read the commented article 'Type‐I interferons mediate the neuroinflammatory response and neurotoxicity induced by rotenone' on page 75 .